Current Role of Open Reconstruction of the Scapholunate Ligament - Luchetti, Riccardo; Atzei, Andrea; Cozzolino, Roberto; Fairplay, Tracy (Journal of Wrist Surgery, 2013)
This paper is a review of the various surgical techniques used in repair or reconstruction of the scapholunate ligament according to the clinical stages and anatomic-pathologic findings. Arthroscopy permits a direct evaluation of the scapholunate injury and the status of the articular surfaces. Specific indications for each type of scapholunate ligament tear are proposed, from the different types of dorsal capsulodesis to bone–ligament–bone techniques and tenodesis procedures. The authors' preferred techniques and literature review of the expected outcomes are presented.
Keywords: SL ligament tear; SL ligament reconstruction; capsulodesis; wrist ligament injury